2016
DOI: 10.1136/tobaccocontrol-2015-052629
|View full text |Cite
|
Sign up to set email alerts
|

Who stops selling? A systematic analysis of ex-tobacco retailers

Abstract: Objective There is evidence that wide distribution of cigarettes contributes to smoking, and multiple commentators have called for a review of tobacco retailing. This study analyses retailers who stop selling cigarettes, why they do so, and discusses the implications for tobacco control. Method An audit of tobacco retailers in the Australian state of NSW was used to identify retailers who had stopped selling tobacco, and they were then compared with current retailers to determine how many, and what types of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 23 publications
(24 reference statements)
3
24
0
Order By: Relevance
“…This is the first systematic analysis of the perceived importance of cigarette sales for alcohol-licenced retailers and confirms results from a smaller NSW study that reported retailers who stop selling tobacco report low (or non-existent) profits from selling tobacco 16. While there was variability in the reported importance of cigarette sales in this study, the results suggest that banning tobacco sales in outlets where alcohol can be consumed may not create significant retailer opposition.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is the first systematic analysis of the perceived importance of cigarette sales for alcohol-licenced retailers and confirms results from a smaller NSW study that reported retailers who stop selling tobacco report low (or non-existent) profits from selling tobacco 16. While there was variability in the reported importance of cigarette sales in this study, the results suggest that banning tobacco sales in outlets where alcohol can be consumed may not create significant retailer opposition.…”
Section: Discussionsupporting
confidence: 83%
“…However, a limitation of only studying retailers who stop selling is that research cannot determine to what extent the same factors may be present for retailers who do not stop selling. For example, the only systematic analysis to date of retailers who have stopped selling tobacco found that declining profits from tobacco sales were generally a necessary but insufficient condition for stopping selling 16. This leaves open the question of whether retailers who still sell tobacco are also experiencing low profits from tobacco sales, thus increasing the likelihood of other retailers leaving the market.…”
mentioning
confidence: 99%
“…In comparison, our understanding of the retail availability of tobacco in Australia is limited. Publications on tobacco retail outlet numbers have been limited to studies in New South Wales, but the once‐off registration scheme in this state (tobacco retailers are required to notify the Ministry of Health only once) means that the true availability of tobacco remains unclear 10 . ‐ 12 Two studies, one each in Western Australia and NSW, explored the distribution of tobacco retail outlets by area remoteness and socio‐economic status, and identified a significant inverse relationship between tobacco outlet density and socio‐economic status 12 , 13 …”
mentioning
confidence: 99%
“…Publications on tobacco retail outlet numbers have been limited to studies in New South Wales, but the once-off registration scheme in this state (tobacco retailers are required to notify the Ministry of Health only once) means that the true availability of tobacco remains unclear. [10][11][12] Two studies, one each in Western Australia and NSW, explored the distribution of tobacco retail outlets by area remoteness and socio-economic status, and identified a significant inverse relationship between tobacco outlet density and socio-economic status. 12,13 The effectiveness of population-level interventions that limit the retail availability of alcohol in reducing alcohol-related harm provides an impetus for exploring similar strategies in tobacco control.…”
mentioning
confidence: 99%
“…The introduction of a substantive annual tobacco licensing fee in South Australia led to an almost 25% decrease in the number of retailers in that state 8 . This is in sharp contrast to New South Wales, where very few tobacco retailers stopped selling after a no‐fee tobacco retailer notification scheme was introduced 9 . As would‐be ex‐smokers report frequent relapsing when they consume alcohol, banning tobacco sales in licensed premises would both reduce the number of tobacco outlets and support quitting smokers where they are most vulnerable 5 .…”
mentioning
confidence: 99%